Local Bi–O bonds correlated with infrared emission properties in triply doped Gd2.95Yb0.02Bi0.02Er0.01Ga5O12 via temperature-dependent Raman spectra and x-ray absorption fine structure analysis. (23rd February 2018) - Tong, Liping; Saito, Katsuhiko; Guo, Qixin; Zhou, Han; Guo, Xingmei; Fan, Tongxiang; Zhang, Di
Abstract: A correlation function between the Raman intensities and the nearest-neighbor mean-square relative displacement (MSRD) σ 2 of local Bi–O bonds is successfully established based on x-ray absorption fine structure (XAFS) and temperature-dependent Raman spectra in the temperature range 77–300 K in amorphous and crystalline Gd2.95 Yb0.02 Bi0.02 Er0.01 Ga5 O12 . The structural symmetries of Gd2.95 Yb0.02 Bi0.02 Er0.01 Ga5 O12 are described by using σ 2 of local Bi–O bonds. More importantly, Gd2.95 Yb0.02 Bi0.02 Er0.01 Ga5 O12 is found to show excellent infrared (IR) emission properties due to changes in Bi–O bonds, and the IR emission intensities are found to depend on σ 2, by using temperature-dependent photoluminescence spectroscopy. The maximum emission intensity at 1533 nm is obtained when σ 2 ∼ 0.003 A ˚ at the lowest symmetry. This work shows that temperature-dependent Raman intensities can be used effectively to analyze the local covalent bonds around absorbing atoms as well as to study the emission properties of this visible-light-activated IR luminophor.